Three Patients, Two Approaches to Illness, and a Question: The DNA of Clinical Wisdom - Davis, Dave (The International Journal of Whole Person Care)

(untitled) (McGill University Library, 2025)
The topic of wisdom raises questions of its meaning in the clinical setting, examined here by describing three patient experiences over a long career, illustrating the need to weigh equally the biomedical and psychosocial aspects of a patient and his or her illness. The patient stories urge the reader to examine the relationship between the two aspects, the role that patient error can play in evoking wisdom, and the bifold, instructive nature of the doctor-patient relationship, a kind of DNA. Finally, the patient stories raise (but do not answer) a question: can clinical wisdom be taught?